Gendered-Caste Discrimination, Human Rights Education, and the Enforcement of the Prevention of Atrocities Act in India (Alberta Journal of Educational Research, 2007)
Despite the constitutional ban on the practice of untouchability and caste-based discrimination, this article elaborates on a gendered-caste-based discriminatory reality in rural India, the difficulties of enforcing legal remedies, and on related human rights praxis to address gendered-caste atrocities by drawing on the experiences of a Canadian voluntary development nongovernmental organization (NGO) that has been working with Dalits (downtrodden/scheduled caste groups) in India for over a decade. This experience suggests that although there is a significant role for human rights education in addressing gendered-caste atrocities, there are cultural and political limits to a rights-based approach that privilege the individual and a politics of vocal, open democratic resistance.